Between being and doing: the implications of health professionals / preceptors in the effectiveness of diabetic self-care (Research, Society and Development, 2020)
This article aims to analyze the personal, professional and ideological implications with the different institutions that permeate the practices of health professionals/preceptors in the realization of the teaching of self-care to diabetics. This is an intervention research, with a qualitative approach, using the theoretical-methodological framework of Institutional Analysis, in its Institutional Socioclinical modality. There were three intervention meetings along the lines of Institutional Socioclinics with the preceptors who develop consultation activities, home visits and educational groups aimed at promoting the self-care of individuals with diabetes mellitus in the Family Health Strategy. The results show that the difficulties of health professionals/preceptors in performing self-care are related to three elements: self-care with self (self), care self-care (self-care) and self-care preceptor (self-care). We consider that this article has opened possibilities for other studies to be carried out in order to effectively manage diabetic self-care, by contributing to a rethink about the actions of health professionals in care and preceptorship and revealing nuances of instituting practices in that space established by women. rules and norms of health and education institutions. Being aware of our limitations and difficulties, and analyzing their implications, can be a facilitator in the development of educational practices related to understanding the other as a being of needs and desires.